Gait analysis of patients with knee osteoarthritis by using elevation angle: confirmation of the planar law and analysis of angular difference in the approximate plane. (17th January 2017) - Ishikawa, Yuki; An, Qi; Nakagawa, Junki; Oka, Hiroyuki; Yasui, Tetsuro; Tojima, Michio; Inokuchi, Haruhi; Haga, Nobuhiko; Yamakawa, Hiroshi; Tamura, Yusuke; Yamashita, Atsushi; Asama, Hajime
Abstract : Evaluating knee osteoarthritis is an important issue. Gait pattern has been suggested to be related to the progression of knee osteoarthritis; however, there are only a few studies elucidating the motion features associated with knee osteoarthritis. Therefore, our objective is to analyze the elevation angle of patients with knee osteoarthritis during gait and to clarify the movement features by an approximate plane of the elevation angle. As a result, the same planar law could be applied to patients with knee osteoarthritis as well as to healthy people. The patients have approximate plane slopes that differ from that of healthy people. Our validation results have shown that these angular differences can distinguish between the patients and healthy people. Graphical Abstract: